Pelatihan pembibitan tanaman hortikultura bagi Komunitas Unsulbar Farming Club (UFC) di greenhouse - Riski, Rafita Firgia; Putra, Ridha Anugerah; Dian, Dian; Alfarizi, Muh. Arya; Rustam, Muh. Risman; Resa, Ignatius (Jurnal Tarreang: Tren Pengabdian Masyarakat Agrokompleks, 2025)
The horticultural plant nursery training using polybags was conducted to enhance the technical knowledge and skills of the Unsulbar Farming Club (UFC) community. The training involved a series of steps, including preparation of planting media, mixing soil and manure, filling polybags, soaking, and transplanting seedlings. The results indicated a 100% success rate, with all participants successfully mastering horticultural nursery techniques using polybags. This training provided a practical solution to address the instability of planting media often encountered in the hydroponic method commonly employed by the UFC community. This activity implies that using polybags can maintain the stability of planting media conditions.